The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnins.2023.1158737
|View full text |Cite
|
Sign up to set email alerts
|

A randomised sham-controlled study evaluating rTMS analgesic efficacy for postherpetic neuralgia

Abstract: ContextPostherpetic neuralgia (PHN) is a refractory neuropathic pain condition in which new treatment options are being developed. Repetitive transcranial magnetic stimulation (rTMS) may have the potential to reduce pain sensations in patients with postherpetic neuralgia.ObjectivesThis study investigated the efficacy on postherpetic neuralgia by stimulating two potential targets, the motor cortex (M1) and the dorsolateral prefrontal cortex (DLPFC).MethodsThis is a double-blind, randomised, sham-controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
4
1
Order By: Relevance
“…It is noteworthy that our study observed that rTMS in both the DLPFC and M1 regions led to a significant reduction in VAS, but no statistical difference was detected between them ( p = 0.98). This finding differs from Wang et al ( 11 ), who suggested that stimulating the M1 region has a more pronounced analgesic effect. This discrepancy may be due to the smaller number of patients included in the M1 group in their experiment, as they only included 20 patients in the M1 group compared to the DLPFC group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that our study observed that rTMS in both the DLPFC and M1 regions led to a significant reduction in VAS, but no statistical difference was detected between them ( p = 0.98). This finding differs from Wang et al ( 11 ), who suggested that stimulating the M1 region has a more pronounced analgesic effect. This discrepancy may be due to the smaller number of patients included in the M1 group in their experiment, as they only included 20 patients in the M1 group compared to the DLPFC group.…”
Section: Discussioncontrasting
confidence: 99%
“…Further scrutiny of the full texts of the remaining 12 articles led to the exclusion of 7 more studies due to dates that could not be extracted ( n = 2), non-randomized control trials ( n = 3) and patient overlap ( n = 2). This process resulted in the selection of 5 randomized controlled trials for the analysis of the efficacy of rTMS in PHN ( 11 , 14 17 ). Figure 1 displays the PRISMA flow diagram depicting this selection process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The keywords less mentioned but with important link strengths were “neuralgia” and “treatment outcome”. This probably shows that some investigators devote their work to understanding the impact of using TMS on the treatment of neuropathic pain, evaluating the resulting outcomes and understanding the impact of using TMS in the treatment of different types of neuropathic pain, such as neuralgia [ 31 ]. In fact, there are studies that suggest that TMS is a reasonable and well-tolerated add-on treatment in neuropathic pain [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%